PERFORMANCE OF DIFFERENT OPEN-POLLINATED BRINJAL VARIETIES GROWN BY ORGANIC AMENDMENTS UNDER EASTERN INDIAN PLATEAU OF JHARKHAND - G. REDDI and A. K. DUTTA*, (The Journal of Research ANGRAU, 2021)
The research was conducted to study the efficiency of organic amendments in seven brinjalcultivars. As organic sources, the performance of liquid manures viz., Sasyagavya, and enrichedSanjeevani were compared with untreated (control) for growing seven open-pollinated varieties namelyHABR-21, Swarna Abhilamb, Swarna Shree, Swarna Shobha, Swarna Pratibha, Swarna Mani, andSwarna Shyamli. Different growth, yield, and quality attributing characters were studied and SwarnaShyamli wasfound to give the highest yield (63.50 t. ha-1) under Enriched Sanjeevani treatment.Besides, Swarna Shree performed well in the expression for growth and yield attributes. Reducingsugar (6.76%) and ascorbic acid content (32.21 mg 100g-1) were found to be the highest in SwarnaMani. In general, Enriched Sanjeevani was observed to be better performing treatment compared toSasyagavya and Untreated (control). Therefore, it might be concluded that Swarna Shyamli andSwarna Shree are suitable brinjal varieties for organic cultivation using Enriched Sanjeevani (10%).